Metabolic engineering of Pseudomonas putida for production of nylon precursors from paper and pulp waste - Lund, Fredrik (Division of Biotechnology and Applied Microbiology, 2025)
Lignocellulosic biomass is an abundant, renewable and low-cost feedstock that plays a key role in the urgent transition from fossil-based resources to renewable and bio-based alternatives used within the chemical industry. Lignin, an aromatic heteropolymer, represents a significant fraction of lignocellulosic biomass, yet it is mainly considered a waste product. Over 50 million tons of Kraft lignin is produced in the paper- and pulp-industry every year where it is mainly burned to generate process heat, electricity and recycle cooking chemicals. However, as the most abundant renewable source of aromatic compounds, lignin has significant potential as a feedstock for production of various chemicals. The utilization of lignin is hindered by its heterogeneity and recalcitrance. As a valorization strategy, the combination of chemical depolymerization with microbial conversion shows promise. Chemical depolymerization is used to release monoaromatic compounds from lignin which typically results in a diverse mixture. Using microorganisms as biocatalysts, this heterogeneous mix can be converted into value-added products. In this thesis work, the goal was to engineer the bacterium Pseudomonas putida KT2440 into efficient biocatalysts for the conversion of Scandinavian lignin streams into muconic acid and adipic acid, precursors for nylon-6,6. Unlike the petroleumbased route to adipic acid, which emits nitric oxide, this lignin-based route offers a renewable alternative that also adds value to paper- and pulp-industry side streams. In one study it was shown that oxidative depolymerization of lignosulfonates, a side stream of sulfite pulping, followed by ethyl acetate extraction yielded a concentrated, low molecular weight fraction suitable for microbial conversion. This fraction consisted mainly of vanillin, which was fully converted to muconic acid, resulting in a 100% yield, by a previously constructed P. putida strain. Vanillin and guaiacol are major depolymerization products of Kraft lignin. While vanillin is a natural substrate of P. putida, it cannot assimilate guaiacol. To address this, a new vanillin assimilation route, which also incorporated guaiacol, was established in P. putida KT2440. Specifically, a vanillic acid decarboxylase was introduced and the native vanillate O-demethylase was deleted to enable conversion of vanillic acid to guaiacol. Introduction of a guaiacol demethylase enabled further conversion into catechol and muconic acid. Native genes catBC were deleted to prevent assimilation of muconic acid, ensuring product accumulation. This led to a muconic acid production of 7.3 mM from 5 mM each of vanillin and guaiacol, which was further improved to 11.1 mM, and a 93% yield, by changing co-substrate to the highly reduced oleic acid. Oleic acid, which can be sourced from non-food waste streams within the food industry (e.g. waste cooking oil), was thus shown to be an efficient substitute for glucose, providing additional flexibility when building future multi-substrate biorefinery concepts. 9 P. putida KT2440 is an obligate aerobe and catabolism of aromatic compounds is an aerobic process. Supply of oxygen is a limiting factor of large-scale bioprocesses, particularly at high cell densities. As a strategy to improve the performance of P. putida KT2440 under oxygen limitation, the use of recombinant hemoglobin, acting as an oxygen carrier, was explored. Two plant hemoglobin genes were expressed in P. putida KT2440 which led to improved growth on glucose at low and high aeration. However, when combined with a recombinant guaiacol demethylase, a negative impact on growth, guaiacol conversion and muconic acid production was observed. The cause of this deleterious effect remains to be elucidated but is speculated to be competition for either heme or oxygen between the two proteins. Lastly, a biocatalyst for the conversion of muconic acid to adipic acid was constructed by introducing an oxygen-sensitive enoate reductase that catalyzes the hydrogenation of muconic acid to adipic acid. By splitting the pathway across two strains and using a two-stage process to accommodate the oxygen-sensitivity, guaiacol was converted to adipic acid at a yield of 60%. The results of this thesis demonstrate that coupling chemical depolymerization to microbial conversion is a viable approach for lignin valorization into adipic acid. Each individual step was demonstrated at laboratory scale. However, several challenges related to biocatalyst performance at large-scale remain to be addressed before an industrial process can be realized.